(untitled) (Revista de Biología Marina y Oceanografía, 2019)
Three species of Carangidae family were caught incidentally during collection of cannonball jellyfish (Stomolophus meleagris) in Bahía de La Paz, Gulf of California, Mexico. All fish were measured, preserved and identified as post flexion larvae and early juvenile of Chloroscombrus orqueta, Hemicaranx leucurus and Caranx caballus. C. orqueta stood out in frequency and abundance. H. leucurus were found only in autumn, while the others were present in different seasons. This is the first time recording H. leucurus and C. caballus associating with cannonball jellyfish. Further studies must evaluate this association as all fish caught were at vulnerable stages, and must be considered in jellyfish fishery management.